The changing relationship between the Scholarship of Teaching (and Learning) and universities - Vardi, Iris (Routledge, 2011)
This paper contextualises this special issue on the relationship between institutions of higher education and the Scholarship of Teaching and Learning (SoTL). It provides an overview of SoTL’s gradual incorporation into institutions in a time of wide ranging educational and political change. Through this discussion it examines the place and the relevance of SoTL to universities predominantly in the western world. In so doing, it lays the basis for the papers in this issue which examine how various institutions have responded to, promoted, developed and incorporated SoTL into their processes, how well SoTL has aligned with institutional objectives, the institutional challenges in addressing SoTL and the implications for SoTL for the future.